Contrato de informação do jornalismo no ecossistema midiatizado: estratégias semiolinguísticas da instância de produção no facebook - Carvalho, Luciana Menezes (2015)
This research aims to understand how the journalism production instance processes the communication contract (Charaudeau [1997], 2009) in social media, through the analysis of semio-linguistic strategies. It is delimited to publications (posts) of the pages (fanpages) maintained by four Brazilian news organizations on Facebook - Estado de S. Paulo, O Globo, Folha de S. Paulo and Zero Hora. The objectives are to map out the main features and functionalities of Facebook as digital social media device for journalism; identify in the speech, the external and internal information data on contract of communication presents in selected pages; recognize semio-linguistic strategies developed by pages in their posts; and contribute to extend to digital social media devices the methodology proposed by Charaudeau for the study of communication contract. The methodological approach includes the exploratory observation of the pages, selection and categorization of publications in two periods (February-June 2014 and the same period of 2015) and applying semio-linguistic analysis protocol to a week composed of every page in 2015. In addition to strength the role of providing information in your posts, pages explore characteristics of social media. They could be identified as the agency marks between journalism and Facebook conversational language, relational purpose, and self-referential purpose. The results may point out the presence of hybrid relations between social media and informative contract, which develop through socio-technical associations, in a typical mediatized ecosystem process.